The Implementation of Cloud Enterprise Resource Planning by Snell X in Manufacturing Process Strategy: A Case Study of Skincare’s Company - Jakfat Haekal; Muhammad Isa Lutfi; Muhammad Kholil; Khairul Nizam Mohd Yunus; Rizaldi Mu’min (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2023)
In the midst of the growing awareness of the Indonesian people to use skincare products from various manufacturers, Company X is one of the SMEs involved in it. Skincare products are sensitive products that can have a direct impact on the wearer. The risk in the skincare business is that Company X must ensure that all materials and production processes are carried out safely and according to procedures. Meanwhile, Company X must also pay attention to maximizing existing resources, including time efficiency. Through this problem, Company X decided to implement an ERP system in its manufacturing process. The purpose of this research is to find out how the process takes place on the production side if it is implemented into the ERP system, as well as observe the benefits and challenges that will be faced by Company X. The method used in this research is qualitative with systematic review which will be described descriptively by conducting direct observations. As a result, the manufacturing process runs normally with the use of several new terms in the system, besides that several advantages are found such as cutting time and costs, however, regarding the limitation, this research only mentions time efficiency advantage. Due to the new system, the adaptation of employees and the high cost of maintaining the system will be the challenges for Company X.